PENGARUH PENAMBAHAN CAMPURAN SERBUK KAYU TERHADAP KUAT TEKAN BETON - Fajar Nugroho; Silta Yulan Nifen (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Concrete is the main material for construction that is widely used. Many studies have been carried out to improve the properties of concrete, especially in terms of strength, durability and workability. Attempts to increase the strength of concrete include adding sawdust to the concrete mixture. This study aims to determine the compressive strength of concrete using sawdust as a fine aggregate additive and to determine the optimum weight of a mixture of sawdust as a fine aggregate additive. Variations in the mixture of sawdust used were 5 gr, 7 gr, 10 gr and 15 gr. The amount of cement used was 381,82 kg/m³ with a Fas of 0,55 and a concrete weight of 2.395 kg/m³. Concrete testing was carried out at the age of 28 days with a total of 15 specimens. Treatment is done by immersion. From the results of testing the compressive strength of concrete with design quality fc' 25 MPa with a mixture of sawdust 5 gr, 7 gr, 10 gr and 15 gr, the results obtained were 26,23 MPa, 26,42 MPa, 26,99 MPa and 27,93 MPa. In this study it can be seen that concrete using sawdust as a fine aggregate added material can increase the compressive strength value of concrete provided that the sawdust used is the finest grain that passes sieve no.100.